Mapping of heavy metal contamination In alluvial soils of the Middle Nile Delta of Egypt - Shokr, Mohamed S.; Baroudy, Ahmed A. El; Fullen, Michael A.; El-Beshbeshy, Talaat R.; Ali, Ramadan R.; Elhalim, Abd; Guerra, Antonio J. T.; Jorge, Maria C. O. (Journal of Environmental Engineering and Landscape Management, 2016)
Areas contaminated by heavy metals were identified in the El-Gharbia Governorate (District) of Egypt. Identification used remote sensing and Geographical Information Systems (GIS) as the main research tools. Digital Elevation Models (DEM), Landsat 8 and contour maps were used to map physiographic units. Nine soil profiles were sampled in different physiographic units in the study area. Geochemical analysis of the 33 soil samples was conducted using X-ray fluorescence spectrometry (XRF). Vanadium (V), nickel (Ni), chromium (Cr), copper (Cu) and zinc (Zn) concentrations were measured. V, Ni and Cr concentrations exceeded recommended safety values in all horizons of the soil profiles, while Cu had a variable distribution. Zn concentrations slightly exceeded recommended concentration limits. Concentrations were mapped in each physiographic unit using the inverse distance weighted (IDW) function of Arc-GIS 10.1 software. Pollution levels were closely associated with industry and urban areas.